مخاطر السرقة العلمية وآليات مكافحتها - نسيب أحمد; حفوظة الأمير عبد القادر (University Of Eloued جامعة الوادي, 2023)
Despite the prevalence of the phenomenon of thefts in recent years, but there is recognition of the phenomenon, even to varying degrees; among those who reduce the intensity of penetration among students, professors and university staff, and the absolute bells of warning, about the dangers of the phenomenon that threaten the reputation and image of the university certificate, and with the proliferation of the phenomenon Copy of the paste, which is the result of many university students during the preparation of graduation certificates, which made one note repeated several times literally, and the causes of the spread of infection of thefts and the scientific deterioration in general at the Algerian University, is the absence of supervision and follow-up and decline moral and soul , And the resignation of society from the university system, which led to the emergence of a major imbalance in the values ladder, the street appreciates the wealth more than the scientific crop, a formula that necessarily leads to negative phenomena, which led to the higher education sector efforts to eliminate them through the establishment of preventive measures and deterrent Including the obligation of the owners of scientific research, including letters of leave to deposit before and after the discussion of the thesis, in addition to the opening of a website in order to identify these scientific research.
The techniques to avoid plagiarism
مداخلة
Keywords: السرقة العلمية; المخاطر; آليات المكافحة; risk; scientific theft; control mechanisms